A facile approach to preparing personalized cancer vaccines using iron-based metal organic framework - Li, Xia; Hattori, Shinya; Ebara, Mitsuhiro; Shirahata, Naoto; Hanagata, Nobutaka (Frontiers in Immunology, 2024)
Background Considering the diversity of tumors, it is of great significance to develop a simple, effective, and low-cost method to prepare personalized cancer vaccines. Methods In this study, a facile one-pot synthetic route was developed to prepare cancer vaccines using model antigen or autologous tumor antigens based on the coordination interaction between Fe3+ ions and endogenous fumarate ligands. Results Herein, Fe-based metal organic framework can effectively encapsulate tumor antigens with high loading efficiency more than 80%, and act as both delivery system and adjuvants for tumor antigens. By adjusting the synthesis parameters, the obtained cancer vaccines are easily tailored from microscale rod-like morphology with lengths of about 0.8 μm (OVA-ML) to nanoscale morphology with sizes of about 50 80 nm (OVA-MS). When cocultured with antigen-presenting cells, nanoscale cancer vaccines more effectively enhance antigen uptake and Th1 cytokine secretion than microscale ones. Nanoscale cancer vaccines (OVA-MS, dLLC-MS) more effectively enhance lymph node targeting and cross-presentation of tumor antigens, mount antitumor immunity, and inhibit the growth of established tumor in tumor-bearing mice, compared with microscale cancer vaccines (OVA-ML, dLLC-ML) and free tumor antigens. Conclusions Our work paves the ways for a facile, rapid, and low-cost preparation approach for personalized cancer vaccines.